U.S. Marines and NATO’s Northern Flank - Strauss, Lon; Gordinier, Ryan; Byrne, Michael (Arctic Review on Law and Politics, 2022)
The U.S. Department of the Navy released A Strategic Blueprint for the Arctic on 5 January 2021. The Navy is focused on preparing for an Alaskan and “Blue” Arctic. Recognizing the changing landscape of the Arctic, the US Navy seeks to maintain a competitive edge, freedom of the seas, and deterrent effect. For the Marine Corps, both the 2021 document and the previous Advantage at Sea: Prevailing with Integrated All-Domain Naval Power, highlight the Marines’ mission to assist the Navy in sea control and sea denial. These strategic documents reflect the direction both the Navy and Marine Corps are taking to better engage in the Arctic, and, therefore on NATO’s northern flank and elsewhere in the world. The Marine Corps’ new concept for warfighting, represented in The Tentative Manual for Expeditionary Advanced Base Operations (EABO) presumes that Marines are a “stand-in” force, i.e., they are already in areas within an adversary’s weapon’s engagement zone (WEZ). However, this is not the case on NATO’s northern flank, where Marines conduct training with NATO and under bilateral agreements. In order to better understand how these new concepts and strategic documents influence the USMC’s engagement on NATO’s northern flank, it is important to relate them to the overall strategic context in this region, as well as the possible gaps that exist down to include operational and some tactical levels implications.